Principles of controlled maintenance management - Johnson, P. Dale (Fairmont Press, 2002)
An effective, well-managed maintenance programme is crucial to the efficient and economical performance of any type of facility. This book presents a complete, step-by-step guide to systematically improving overall maintenance operations, covering maintenance organization, inventory, continuous inspection, planning, scheduling and programme management. The presentation is structured in a manner which allows the reader to utilize basic guidelines in implementing a management system which can be customized to the specific requirements and goals of his/her plant or facility.